Assessing Indigenous Forest Management in Mount Merapi National Park Based on Ostrom’s Design Principles - Depari, Catharina (Forest and Society, 2023)
Despite their abundant potential to support the current understanding of environmental changes and improve natural resource management, Indigenous Peoples remain excluded from policymaking. Such marginalization partly stems from the formal government-driven adoption of colonial-style controls over natural resources, which historically had marginalized local populations politically and economically. Using the case of the Pelemsari sub-village, this article attempts to analyze the robustness of Common-Pool Resource institutions in Mount Merapi National Park according to Ostrom’s design principles. The methods used for this purpose are participant observation, document reviews, and semi-structured interviews. The research findings indicate social capital as the main factor that contributes to the local institution’s robustness. Nevertheless, the principles corresponding to authority suggest challenges of engaging communities in reforestation and conservation programs. The shortcomings in these principles contributed to the people’s slow recovery and ongoing degradation of forest diversity in Mount Merapi after the eruption in 2010.